Oxygen dependence of the cytotoxicity and metabolic activation of 4-alkylamino-5-nitroquinoline bioreductive drugs. - Siim, B. G. (Nature Publishing Group, 1994)
The cytotoxic potency of 4-alkylamino-5-nitroquinoline drugs in AA8 cell cultures is enhanced up to 60-fold under hypoxia, with wide variations in selectivity for hypoxic cells observed for different members of this series. This study uses three representative 5-nitroquinolines to examine whether these differences in hypoxia-selective cytotoxicity are cell line specific, and to explore quantitatively the oxygen dependence of the cytotoxicity and metabolism of these compounds. The parent compound 5NQ, its 5NQ, its 8-methyl analogue (8Me5NQ) and the 8-methylamino analogue (8NHMe-5NQ) each showed similar hypoxic selectivity (ratio of concentration x time for 90% kill for zero versus 20% oxygen of 13-18-, 30-69- and 1.2-1.4-fold respectively in the three cell lines tested (AA8 Chinese hamster ovary, EMT6/Ak mouse mammary tumour and FME human melanoma). The cytotoxicity and metabolism (covalent binding) of radiolabelled 8Me-5NQ was investigated in AA8 cultures over a range of oxygen tensions (0-95%). The oxygen tension in solution required for 50% inhibition of log cell kill or adduct formation observed under anoxia (C50) was 0.01 and 0.02% oxygen respectively, suggesting that bioreductive alkylation is the mechanism of 8Me-5NQ toxicity. The K-value (oxygen concentration for cytotoxic potency equal to the mean of the potencies at zero and infinite oxygen) was similar (0.02% oxygen). Calculations based on measured rate constants for formation of the nitroradical anion of 8Me-5NQ and rates of radical loss through disproportionation or reaction with oxygen, predict a K-value for 8Me-5NQ of 0.025% oxygen, in good agreement with the experimentally determined value. Modelling of cell killing expected by the combination of 8Me-5NQ plus radiation suggested that tumour cells at intermediate oxygen tensions (0.01-1%) will be partially resistant to this treatment, and would limit the use of these 5-nitroquinolines in combination with radiation, unless sufficient drug could be delivered to cause extensive killing in the anoxic compartment.